Penerapan Teknik Partisi Langkah Kuda Papan Catur pada Pelabelan Super (a,d)-P_2 (▷) ̇ H-Antimagic Total Covering Sebarang Dua Graf dan Aplikasinya - A H Rahmatillah; I H Agustin; Dafik Dafik (jcgant, 2022)
Let be a finite collection of simple, nontrivial and undirected graphs. A graph is as antimagic total covering if there is bijectif function for every subgraph in which isomorfic to and the total weight, form arithmetic sequence , in which a,b are integers and n is a number of graph cover of which the result of total comb product operation. A antimagic total covering is as